Targeted therapy for mTORC1-driven tumours through HDAC inhibition by exploiting innate vulnerability of mTORC1 hyper-activation - Yang, Fuchun (Br J Cancer, 2020)
BACKGOUND: The mechanistic target of rapamycin complex 1 (mTORC1) is important in the development and progression of many cancers. Targeted cancer therapy using mTORC1 inhibitors is used for treatment of cancers; however, their clinical efficacies are still limited. METHODS: We recently created a new mouse model for human lymphangiosarcoma by deleting Tsc1 in endothelial cells and consequent hyper-activation of mTORC1. Using Tsc1(iΔEC) tumour cells from this mouse model, we assessed the efficacies of histone deacetylase (HDAC) inhibitors as anti-tumour agents for mTORC1-driven tumours. RESULTS: Unlike the cytostatic effect of mTORC1 inhibitors, HDAC inhibitors induced Tsc1(iΔEC) tumour cell death in vitro and their growth in vivo. Analysis of several HDAC inhibitors suggested stronger anti-tumour activity of class I HDAC inhibitor than class IIa or class IIb inhibitors, but these or pan HDAC inhibitor SAHA did not affect mTORC1 activation in these cells. Moreover, HDAC inhibitor-induced cell death required elevated autophagy, but was not affected by disrupting caspase-dependent apoptosis pathways. We also observed increased reactive oxygen species and endoplasmic reticulum stress in SAHA-treated tumour cells, suggesting their contribution to autophagic cell death, which were dependent on mTORC1 hyper-activation. CONCLUSION: These studies suggest a potential new treatment strategy for mTORC1-driven cancers like lymphangiosarcoma through an alternative mechanism.